Implementasi ISPS Code Terkait Dengan Pelaksanaan Drill dan Exercise di Pelabuhan Tanjung Emas - Fitri Kensiwi; Atria Maharani; Riyanto Riyanto (Politeknik Ilmu Pelayaran Semarang, 2022)
Indonesia has ratified the International Convention for the Safety of Life at Sea (SOLAS Convention) and is now making plans for the security of port facilities, building facilities, installing equipment for security, training security officers, and so on based on the ISPS Code. However, there are still problems that arise, such as the lack of facilities and equipment for security and the performance of the security system which is still considered inadequate. This study aims to determine the need for the implementation of ISPS Code drill and exercise, as well as to determine the effect of the ISPS Code implementation related to the implementation of the drill and exercise on security at Tanjung Emas Port. Qualitative descriptive method that describes the implementation of the ISPS Code related to implementation of drill and exercise at the Port of Tanjung Emas Semarang. The data then analyzed using interactive analysis techniques from Miles and Huberman. The results of the study indicate that the drill and exercise activities need to be implemented at the Port of Tanjung Emas Semarang, as well as drill and exercise activities in accordance with the requirements. that have an effect on the ability to implement the ISPS Code.